An ecocritical reading of Ursula K. Le Guin's children's fiction - Doherty, Peter (Trinity College (Dublin, Ireland). School of English, 2015)
This dissertation articulates an ecocritical reading of Ursula K. Le Guin’s fiction for children, in particular her Earthsea sequence. Focusing on the formal narrative and visual structures that Le Guin uses to represent nature, this dissertation argues that there is a fundamental contradiction in the author’s aesthetic. On the one hand, Le Guin’s texts appear to offer a vision in which the human/nature distinction is mitigated. On the other hand, Le Guin is shown to tacitly reinscribe the distinction between the human and nonhuman.
Embargo End Date: 2022-01-01
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin, 2015